If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-4=5(x+2)
We move all terms to the left:
4x-4-(5(x+2))=0
We calculate terms in parentheses: -(5(x+2)), so:We get rid of parentheses
5(x+2)
We multiply parentheses
5x+10
Back to the equation:
-(5x+10)
4x-5x-10-4=0
We add all the numbers together, and all the variables
-1x-14=0
We move all terms containing x to the left, all other terms to the right
-x=14
x=14/-1
x=-14
| 4x+6x=3-8 | | 3(5+6x)=18x+15 | | 2r–15=-9r+18 | | 8x-2=-9+7× | | −12(4n+2)=19 | | -11-(-26)=x/12 | | (2x+5)+(6x-18)=180 | | 52=4y-16 | | 1/7=14-2x | | 15(9x-1)-14=133x+15 | | 7x-(2x-10)=25 | | 75=5w+13 | | 4/3=4n | | 2x*(x-2)=7x^2-7x | | 15x-15=7×-13 | | 2x+4+60=90 | | 13=7+3r | | x-1/2=-1/2 | | -2x+12=3x-103 | | x+1.5−0.5x=4.5x+1.5-0.5x=4.5 | | 2+2s=14 | | 54=4y-16 | | 4(x^2+19x+70)=544 | | -18x^2+19x-5=0 | | n/2=3/5 | | =52−4y16 | | 9x+2=7x-24 | | 13=9r+8 | | 2x-1/3x=0 | | -9x^2-9x+28=0 | | -3d+21=6 | | 2(2x-2)=9x |